Factors affecting accounting practices in SMEs / Dwi Pertiwi Anggraini … [et al.] - Anggraini, Dwi Pertiwi; Suginam, Suginam; Utomo, Dito Putro; Amelia, Dede; Listiorini, Listiorini; Rahayu, Sri; Ningsih, Heny Triastuti Kurnia (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2023)
Micro, Small and Medium Enterprises (MSMEs) are currently growing rapidly in Indonesia. However, MSME actors have not carried out accounting practices. MSME actors still carry out simple bookkeeping. This research is a quantitative research. The purpose of this study was to determine the effect of the level of education, the level of awareness of doing accounting and facilities and infrastructure on accounting practices in MSMEs in Tanjung Morawa District. The population in this study were all SMEs in Tanjung Morawa District, totaling 672 SMEs. The number of samples was determined using Simple Random Sampling, so that 20 SMEs were obtained as samples. The data collection technique in this study was to use a questionnaire. And the data analysis technique used is to perform multiple linear regression analysis. The results of this study stated that for the variable level of education.